PATENT AND LICENSES ECONOMIC EFFICIENCY - Nozimov E. A.; Khujakulova Sevinch (Ecominds Press, 2025)
This the article is a patent and licenses enterprises in the activity how economic importance has is considered . Innovative ideas protection to do , to compete advantage storage and new technologies at the market application in the process patenting system place analysis as will go Also , license to give or to take through enterprises how additional to income has to be , expenses abbreviation and to the market entrance opportunities expansion examples based on showing It will be passed .
Keywords: Intangible assets modern enterprise in the activity important place They are material to form has not , but enterprise value increasing and competitiveness provider resources . Therefore , intangible assets determine , assess and into account to take issues economy and finance in the field big importance has . This article intangible of assets types , their economic value determination methods and enterprise in the activity role to study focused .